An in vitro demonstration of overcoming drug resistance in SKOV3 TR and MCF7 ADR with targeted delivery of polymer pro-drug conjugates. (28th May 2017) - Bhattarai, Prashant; Vance, Dylan; Hatefi, Arash; Khaw, Ban An
Abstract: Drug resistance is a common phenomenon that occurs in cancer chemotherapy. Delivery of chemotherapeutic agents as polymer pro-drug conjugates (PPDCs) pretargeted with bispecific antibodies could circumvent drug resistance in cancer cells. To demonstrate this approach to overcome drug resistance, Paclitaxel (Ptxl)-resistant SKOV3 TR human ovarian- and doxorubicin (Dox)-resistant MCF7 ADR human mammary-carcinoma cell lines were used. Pre-targeting over-expressed biotin or HER2/neu receptors on cancer cells was conducted by biotinylated anti-DTPA or anti-HER2/neu affibody – anti-DTPA Fab bispecific antibody complexes. The targeting PPDCs are either D-Dox-PGA or D-Ptxl-PGA. Cytotoxicity studies demonstrate that the pretargeted approach increases cytotoxicity of Ptxl or Dox in SKOV3 TR or MCF7 ADR resistant cell lines by 5.4 and 27 times, respectively. Epifluorescent microscopy – used to track internalization of D-Dox-PGA and Dox in MCF7 ADR cells – shows that the pretargeted delivery of D-Dox-PGA resulted in a 2- to 4-fold increase in intracellular Dox concentration relative to treatment with free Dox. The mechanism of internalization of PPDCs is consistent with endocytosis. Enhanced drug delivery and intracellular retention following pretargeted delivery of PPDCs resulted in greater tumor cell toxicity in the current in vitro studies.